Effectiveness of Role-Playing Method and Interactive Video Media on Students' Speaking Ability in Class IV Elementary School - Septiani, Shilfi; Khusaini, Fakhri; Fatimah, Nunung (Journal of Educational Sciences, 2025)
The low speaking skills of elementary school students, such as difficulty composing sentences, limited vocabulary, and lack of confidence, are challenges in learning Indonesian. This study aims to determine the effect of the role playing method assisted by interactive video media on the speaking skills of grade IV students at SDN 32 Panggi Bima City. The method used is pre-experimental with a one group pretest-posttest design. The research sample amounted to 29 students who were selected through the total sampling technique. The instruments in the form of oral tests and observation sheets have been tested for validity and reliability with Cronbach's Alpha values of 0.928 (pretest) and 0.975 (posttest). The results of the analysis showed an increase in the average score from 55.48 to 79.14. The Wilcoxon Signed Ranks test yielded a value of Z = -4.705 and a significance of 0.000 (p < 0.05), which showed a significant difference between the pretest and the posttest. All students experienced improved speaking skills. Thus, the role playing method combined with interactive video media has proven to be effective in improving students' pronunciation skills, fluency, and confidence in speaking. This model is recommended as an innovative and fun Indonesian learning strategy.